A Comparison of Mental Toughness in Skilled and Novice Climbers - Fatemeh Rezaee; Fazlolah Bagherzadeh; M.Hossein Sadeghzadeh (University of Tehran, 2017)
Mental toughness is the ability to increase the flow of the positive energy against obstacles. The aim of the present study was to compare mental toughness of male and female skilled and novice climbers. 130 climbers that were randomly selected and divided to skilled and novice groups. Data were collected through Mental Toughness Questionnaire of Sheard, Golby and Van Wersch. Data were analyzed using multivariate analysis of variance and LSD post hoc test (P≤0.05). The results showed that the main effect of skill was not significant but the main effect of gender and interaction between gender and skill were significant. Further analysis on the data showed that the highest mean belonged to the male skilled climbers in confidence component and the lowest mean belonged to female novice climbers in control component. Male skilled climbers were also significantly higher in all three subscales of confidence, control, and stability than female skilled climbers. So, it is suggested that according to the nature of climbing which is an endurance and risky exercise, merely being skilled at developing the mental toughness of climbers was not a criterion and other factors such as gender and its interaction with skill play an important role as well.